2013
DOI: 10.7763/ijet.2013.v5.567
|View full text |Cite
|
Sign up to set email alerts
|

Secure Lightweight Pairing-Based Key-Agreement Cryptosystems: Issues and Challenges

Abstract: Abstract-Although a large number of pairing-based key-agreement cryptosystems have been proposed, there are still a lot of drawbacks. One of the most important disadvantages of mentioned cryptographic functions is that there is not a comprehensive system to satisfy both security and efficiency requirements. Moreover, there is not an integrated document to categorize and present possible challenges. Therefore, we paid particular attention to this issue, unlike other surveys in the area of key-agreement cryptosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Motivated by what pointed above, cryptography research community have concluded that the use of Elliptic Curve Cryptography (ECC) is the golden key to make public key cryptosystems lightweight in order to make them appropriate for resource constrained platforms [7]. As an example, we can refer to the result of what studied by Tan et al [13] who compared the energy cost of two popular Public-Key cryptosystems, RSA and ECC.…”
Section: A Progressive History Of Making Cryptographic Schemes LImentioning
confidence: 99%
See 4 more Smart Citations
“…Motivated by what pointed above, cryptography research community have concluded that the use of Elliptic Curve Cryptography (ECC) is the golden key to make public key cryptosystems lightweight in order to make them appropriate for resource constrained platforms [7]. As an example, we can refer to the result of what studied by Tan et al [13] who compared the energy cost of two popular Public-Key cryptosystems, RSA and ECC.…”
Section: A Progressive History Of Making Cryptographic Schemes LImentioning
confidence: 99%
“…Mentioned reasons above were sufficient to persuade a large group of developers to find a solution to make public key cryptosystems feasible in resource-constrained platforms [7]. To make the use of public key cryptosystems feasible in such resource constrained environments, it is possible to refer to what Gaubatz et al proposed in [10].…”
Section: A Progressive History Of Making Cryptographic Schemes LImentioning
confidence: 99%
See 3 more Smart Citations